2019
DOI: 10.1093/cdn/nzz048.p11-063-19
|View full text |Cite
|
Sign up to set email alerts
|

First Feeding Behaviors of Native Hawaiian, Pacific Islander, and Filipino Infants (P11-063-19)

Abstract: Objectives The objective of this study was to describe the first feeding behaviors (breastfeeding and complementary feeding timing) of Native Hawaiian, Pacific Islander, and Filipino infants 3 – 12 months of age. Methods A convenient sample of Native Hawaiian, Pacific Islander, and Filipino infants ages 3 – 12 months were recruited for this study examining dietary diversity and the feasibility of a mobile phone food record. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Hawaii, the consumption of iron-rich foods was lower than in the United States; only 28% started CF * with iron-fortified cereals [57].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In Hawaii, the consumption of iron-rich foods was lower than in the United States; only 28% started CF * with iron-fortified cereals [57].…”
mentioning
confidence: 93%
“…In Hawaii, one study conducted among Native Hawaiian, Latino, and Pacific Islanders showed low prevalence of early CF (6%) [57].…”
mentioning
confidence: 99%
“…For infants 3-12 months old there is a global metric, the Minimum Dietary Diversity (MDD) score, developed by the World Health Organization (WHO). (3) An example of its use was applied to infants 3-12 months old living in Oahu, Hawaii to provide an indication of complementary feeding practices and healthfulness of the infant diet. The majority of the care takers noted the first food was poi (steamed mashed taro with water) or infant cereal, however overall approximately 25% of infants 6-12 months of age met the recommended score of the MDD.…”
mentioning
confidence: 99%